The effect of using cooperative learning model type of examples non examples and motivation toward student learning outcomes - Aulia Rahuma; Azwar Ananda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This research aims to find out : (1) the differences outcomes learning of the social student subject between student taught by using example non example model and student taught by using convensional model (2) the differences outcomes learning of the social student subject between student taught by using example non example model with convensional models by looking from leaarning motivation. (3) the influence of interaction between example non example models  with convensional models. This study is an experimental research  (qasi-experiment) with a  2x2 factorial design.  Analysis data in this  research was  use anava statistical test. Research finding suggest that : (1) there are differences outcomes learning of the social student subject between student taught by using example non example model and student taught by using convensional models (2) the students which have  high motivation in learning that  given  by example non example models socialstudent subject are higher  than convensional models  students. (3)  the students which have low motivation in learning outcomes learning of the social student are higher given  by using  conventional models than use example non example models. (4) there is an influence of interaction between example non example models  with convensional models with learning motivation ( high – low) on  the result of  social student subject.